Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/adma.201405495
|View full text |Cite
|
Sign up to set email alerts
|

Relaxor Ferroelectric‐Based Electrocaloric Polymer Nanocomposites with a Broad Operating Temperature Range and High Cooling Energy

Abstract: Electrocaloric nanocomposites simultaneously derive high electrocaloric strength from inorganic inclusions and high dielectric strength from the polymer matrix to display a pronounced electrocaloric effect (ECE). By designing the inorganic filler and polymer matrix, which are both relaxor ferroelectrics with the ambient-temperature phase transition and minimized hysteresis, a large ECE becomes accessible with high cooling efficiency over a broad temperature range at and near room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
87
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(97 citation statements)
references
References 34 publications
2
87
0
Order By: Relevance
“…As a result, the refrigeration effect of ferroelectrics is achieved. Although giant ECEs have been found in ferroelectric polymers, ceramics and polymer-ceramic composites, much effort is still devoted to developing those novel electronic materials which could possess large ECE entropy change [3][4][5][6][7][8][9]. Remarkably, some ferroelectric materials exhibit abnormal ECE which is in contrast to those aforementioned, suggesting that cooling occurs in the ECE materials with the application of an electric field and heating occurs in the materials with its removal.…”
Section: Introductionmentioning
confidence: 51%
“…As a result, the refrigeration effect of ferroelectrics is achieved. Although giant ECEs have been found in ferroelectric polymers, ceramics and polymer-ceramic composites, much effort is still devoted to developing those novel electronic materials which could possess large ECE entropy change [3][4][5][6][7][8][9]. Remarkably, some ferroelectric materials exhibit abnormal ECE which is in contrast to those aforementioned, suggesting that cooling occurs in the ECE materials with the application of an electric field and heating occurs in the materials with its removal.…”
Section: Introductionmentioning
confidence: 51%
“…A number of studies have reported ceramic/polymer nanocomposites with high energy density 6, 7. For example a discharge energy density of 20 J cm −3 at 646 kV mm −1 was reported for BaTiO 3 @TiO 2 core–shell fibers in a polyvinylidene fluoride polymer matrix (denoted as BaTiO 3 @TiO 2 /PVDF, where @ denotes a core–shell structure) 8.…”
mentioning
confidence: 99%
“…Table 1 summarizes the performance of some typical polymer‐based dielectric composites with the electric field. The large energy density at such a low electric field in these nanocomposites can be attributed to (i) the dual phase nature of the TiO 2 @PZT nanowire array, which results in large interfacial regions and hence large interfacial polarization;24, 25 (ii) the highly oriented nanowire also plays an important role in increasing the polarization and electromechanical coupling of the nanocomposites;6, 16 and (iii) the obtained high permittivity of the nanocomposites yields high saturation polarization (Equation (3)), and the nanocomposites possess narrow hysteresis loops with low values of P r as shown in Figures S5–S7 (Supporting Information), which lead to largely enhanced P max − P r values.…”
mentioning
confidence: 99%
“…In comparing with the inorganic materials, highperformance polymers and polymer-based composites (organic materials) show the characteristics of lightweight, flexibility, and resistance to acid and alkali as well as easy processing [24,25]. As a result, these organic materials are tremendously studied as dielectrics to replace the inorganic materials [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the relative permittivity of the polymer can be effectively improved through the introduction of fillers [24]. At present, the fabrication of polymeric composite dielectrics showing high-k, low loss tangent, low density, and good mechanical properties is of great significance to the preparation of new energy storage elements [25].…”
Section: Introductionmentioning
confidence: 99%